NUMBER OF COLIFORM AND NON-COLIFORM BACTERIA IN RETICULUM OMASUM AND ABOMASUM IN BALI CATTLE BASED ON GEOGRAPHICAL DIFFERENCES - Wardani, Ririn Dwi Ratma; Suarjana, I Gusti Ketut; Gelgel, Ketut Tono Pasek (Buletin Veteriner Udayana, 2023)
Bali cattle are germplasm originating from the island of Bali which is the most popular in Indonesia, so it is highly conserved and maintained for its population.       This study aims to determine the level of livestock health, determine the content of good feed for breeders to support the development and increase in the population of Bali cattle in Indonesia. This research was conducted by taking samples at the Slaughterhouse in the form of the stomach contents of Bali cattle consisting of reticulum, omasum, and abomasum. The samples taken were 32 Bali cattle, 16 of which came from the lowlands and highlands. The method used in this study was the cultivation of bacteria on EMBA media using the scatter method. Data on the number of colonies of Coliform and Non-coliform bacteria growing on EMBA media are tabulated in the form of mean ± standard deviation (SD). The data obtained were then analyzed using the Independent sample T-test to determine its significance value. Mean ± SD results of the analysis of the number of bacteria the number of lowland Coliform bacteria, namely reticulum, omasum, and abomasum, namely 54.31±17.469x10 3 CFU/g, 52.63±19.071x10 3 CFU/g, and 59.63±18,011x10 3 CFU/g. While from the highlands, namely: 64.88±14.908x10 3 CFU/g, 61.94±13.056x10 3 CFU/g, and 62.00±12.920x10 3 CFU/g. While non-coliform bacteria from the lowlands were: 50.19±21.182x10 3 CFU/g; 44.38±18.279x10 3 CFU/g, and 38.63±18.998x10 3 CFU/g. The highlands are: 47.63±10.620x10 3 CFU/g, 46.56±13.301x10 3 CFU/g, and 45.00±12.517x10 3 CFU/g. The results of the follow-up study of the Independent Simple T-test showed that the number of Coliform and Non-coliform bacteria from each organ had no significant effect (Sig > 0.05) in the highlands and lowlands. Based on the results of this study, it can be concluded that differences in geographical location have no significant effect on the number of Coliform and Non-coliform bacteria in Bali cattle reared in the lowlands and highlands.